Methods of spectral analysis in mathematical physics : conference on Operator Theory, Analysis and Mathematical Physics (OTAMP) 2006, Lund, Sweden - Janas, Jan. (Springer, 2017)
The volume contains the proceedings of the OTAMP 2006 (Operator Theory, Analysis and Mathematical Physics) conference held at Lund University in June 2006. The conference was devoted to the methods of analysis and operator theory in modern mathematical physics. The following special sessions were organized during the conference: Spectral analysis of SchrAdinger operators; Jacobi and CMV matrices and orthogonal polynomials; Quasi-periodic and random SchrAdinger operators; Quantum graphs